Global Existence and Asymptotic Behavior of Solutions for a Class of Nonlinear Degenerate Wave Equations - Yaojun Ye (Differential Equations and Nonlinear Mechanics)
This paper studies the existence of global solutions to the initial-boundary value problem for some nonlinear degenerate wave equations by means of compactness method and the potential well idea. Meanwhile, we investigate the decay estimate of the energy of the global solutions to this problem by using a difference inequality.